2013
DOI: 10.1103/physreva.87.052140
|View full text |Cite
|
Sign up to set email alerts
|

Quantum state tomography with incomplete data: Maximum entropy and variational quantum tomography

Abstract: Whenever we do not have an informationally complete set of measurements, the estimate of a quantum state can not be uniquely determined. In this case, among the density matrices compatible with the available data, it is commonly preferred that one which is the most uncommitted with the missing information. This is the purpose of the Maximum Entropy estimation (MaxEnt) and the Variational Quantum Tomography (VQT). Here, we propose a variant of Variational Quantum Tomography and show its relationship with Maximu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…Thus, the RρR algorithm [26] can be used to solve the optimization problem. The RρR algorithm works in most of cases, but it has 310 no theoretical guarantee of convergence, regardless the dataset and the initial point [17]. So, in this paper, we decide to use another algorithm [17] proposed under a line search procedure with Armijo condition, namely "Diluted RρR".…”
Section: Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the RρR algorithm [26] can be used to solve the optimization problem. The RρR algorithm works in most of cases, but it has 310 no theoretical guarantee of convergence, regardless the dataset and the initial point [17]. So, in this paper, we decide to use another algorithm [17] proposed under a line search procedure with Armijo condition, namely "Diluted RρR".…”
Section: Learningmentioning
confidence: 99%
“…During the optimization process, the search direction is a combination of 315 two ascent directions controlled by the step size t. In the paper [17], it has shown that an inexact line search method to determine t is enough for finding a value to guarantee the global convergence. The initial density matrix…”
Section: Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same spirit, several algorithms for estimating quantum states from incomplete measurement data have been reported recently [19][20][21][22]. Here, we revisit the problem in the context of mutually unbiased (MU) measurements, which are known to be optimal for state reconstruction [23] if a complete set of bases is to be measured.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efficient quantum state tomography which may overcome these difficult challenges has attracted great attention [19]. The maximum entropy approach can give an approximate estimation for general states [20]. Part parameters, which are much less than the full (d 2 − 1) parameters, are enough to characterize matrix product states (MPS) [19,21,22].…”
Section: Introductionmentioning
confidence: 99%